The genus Isoetes (Isoetaceae): a provisional checklist of the accepted and unresolved taxa - Troia, Angelo; Pereira, Jovani B.; Kim, Changkyun; Taylor, W. Carl (Phytotaxa, 2016)
Isoetes is a widely distributed lycophyte genus of at least 200 species occurring in diverse habitats. The species can be difficult to identify because Isoetes, with its apparent simplicity of form and conserved morphology, provides few diagnostic features to reliably distinguish its species. The last worldwide monograph, published nearly a century ago, listed 77 taxa. The first step in producing a flora or monograph of all known species of a genus is to compile a list of the acceptable species names. The list presented here is a compilation of 192 accepted names representing taxa from regions around the world: chromosome numbers were assigned to 101 of them, with polyploidy settled on 46.7%. Distribution mapping of the accepted species indicates that South America is the center of diversity for Isoetes and species diversity is the highest in temperate regions. Many of the species on this list are rare and have limited ranges. The list of taxa can be used to initiate floristic studies and conservation efforts in keeping with the target goals of the Global Strategy for Plant Conservation.